2018
DOI: 10.1016/j.neulet.2018.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous sensorimotor cortical activity is suppressed by deep brain stimulation in patients with advanced Parkinson’s disease

Abstract: Advanced Parkinson's disease (PD) is characterized by an excessive oscillatory beta band activity in the subthalamic nucleus (STN). Deep brain stimulation (DBS) of STN alleviates motor symptoms in PD and suppresses the STN beta band activity. The effect of DBS on cortical sensorimotor activity is more ambiguous; both increases and decreases of beta band activity have been reported. Non-invasive studies with simultaneous DBS are problematic due to DBS-induced artifacts. We recorded magnetoencephalography (MEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 34 publications
(56 reference statements)
0
32
1
Order By: Relevance
“…DRT significantly increased cortical motor beta band power, thus having a normalizing effect (Heinrichs‐Graham, Kurz, et al, ). In contrast, STN‐DBS lowered alpha and low‐beta band power in the sensorimotor cortex in two studies (both a sensor‐space and a source‐space study) during eyes‐open, resting‐state (Abbasi et al, ; Luoma et al, ). However, no correlation with motor improvement has been observed.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…DRT significantly increased cortical motor beta band power, thus having a normalizing effect (Heinrichs‐Graham, Kurz, et al, ). In contrast, STN‐DBS lowered alpha and low‐beta band power in the sensorimotor cortex in two studies (both a sensor‐space and a source‐space study) during eyes‐open, resting‐state (Abbasi et al, ; Luoma et al, ). However, no correlation with motor improvement has been observed.…”
Section: Resultsmentioning
confidence: 96%
“…Posterior cortical dysfunction seems to play a crucial role here (Boon et al, ; Olde Dubbelink, Hillebrand, Twisk, et al, ; Stoffers et al, ). Treatments such as DRT and rivastigmine generally normalized disrupted neurophysiological characteristics in both research fields, although many discrepancies exist, for example the increase in cortical motor beta power upon DRT (Heinrichs‐Graham, Kurz, et al, ), versus the decrease observed upon DBS (Abbasi et al, ; Luoma et al, ), or the differential effect of DRT on whole‐brain functional connectivity (Cao et al, ; Stoffers, Bosboom, Wolters, et al, ). Potential explanations for these discrepancies include methodological differences and differences in the underlying neurophysiological characteristics between PD patients (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Parkinson's patients treated with electrical deep brain 26 stimulation (DBS) showed an increase in cortical sensorimotor beta power following DBS 27 compared to off treatment (Airaksinen et al, 2012;Cao et al, 2017). However, other studies 28 have reported that DBS leads to a broader suppression of 5-25 Hz power in frontal and 29 sensorimotor cortex (Abbasi et al, 2018;Luoma et al, 2018). 30…”
Section: Introductionmentioning
confidence: 99%